Alianzas Socio-Técnicas y Políticas de Medicamentos: perspectivas desde la crisis Argentina del 2001 - Santos, Guillermo (Pontificia Universidad Católica del Perú, 2024)
The aim of this article is to analyse the problem-solution dynamics linked to the availability of and access to medicines for the Argentine population as a result of the social, economic, political and health crisis that affected Argentina in 2001.It is interesting to analyse the scope, characteristics and limitations of the public policies implemented by the Argentinean government between 2002 and 2008, whose objectives were to solve the problem of the lack of access to medicines that affected the most vulnerable sectors of the Argentinean population.The analytical reconstruction of this socio-institutional dynamic will provide a better understanding of the process of co-construction of public policies, regulations, artefacts, economic interests, ideologies and inclusive techno-productive development dynamics, and will offer new explanations about the functioning/non-functioning of the public policies implemented to solve social problems linked to the population’s access to medicines.This article argues that public policy is not only the exercise of a vertical and centralised will, but rather the result of the alignment and coordination of a heterogeneous set of elements that are horizontally linked and that allow public policies to consolidate or destabilise.This article is framed within a socio-technical approach (Bijker, 1995; Pinch y Bijker, 2008; Thomas, 2008, Santos y Thomas, 2016), which combines analytical tools from constructivist sociology and public policy analysis. The descriptive and explanatory capacity of such an approach derives from the possibility of generating an analytical reconstruction of the complex relationships between users and tools, actors and artefacts, institutions and normative systems, ideologies and economic interests, where in the same act in which public policies are designed and implemented, legal-political orders, social organisations and techno-productive systems are constructed.Two key concepts guide the analysis of this article: ‘functioning/non-functioning’ and ‘socio-technical alliance’. The former is the result of a process of social and normative co-construction in which heterogeneous elements intervene, usually in a self-organised way: material conditions, systems, knowledge, regulations, financing, benefits, etc. It involves complex processes of tailoring responses/solutions to specific and particular historically situated socio-institutional articulations. The second concept, the socio-technical alliance, is an analytical reconstruction of a coalition of heterogeneous elements involved in the process of constructing the functioning/non-functioning of a public policy. In other words, a socio-technical alliance constitutes a movement of alignment and coordination of: artefacts, ideologies, regulations, knowledge, institutions, social actors, economic resources, environmental conditions, materials, etc. that make possible or impede the stabilisation of the socio-technical adequacy of a policy and its functioning.

El objetivo de este artículo es analizar la dinámica problema-solución vinculada a la disponibilidad y acceso de la población argentina a medicamentos como consecuencia de la crisis social, económica, política y sanitaria que afectó a la Argentina en el año 2001.Interesa analizar los alcances, características y limitaciones que tuvieron las políticas públicas implementadas por el gobierno argentino entre los años 2002 y 2008, cuyos objetivos fueron resolver el problema de la falta de acceso a medicamentos que afectaba a los sectores más vulnerables de la Argentina.La reconstrucción analítica de esta dinámica socio-institucional aportará una mejor comprensión del proceso de co-construcción de políticas públicas, normativas, artefactos, intereses económicos, ideologías y dinámicas de desarrollo tecno-productivos inclusivas, y ofrecerá nuevas explicaciones acerca del funcionamiento/no funcionamiento de las políticas públicas implementadas para solucionar problemas sociales vinculados al acceso de la población a medicamentos.Se sostiene en este artículo que la política pública no constituye sólo el ejercicio de una voluntad vertical y centralizada, sino que es más bien el resultado del alineamiento y coordinación de un conjunto heterogéneo de elementos que se vinculan horizontalmente y que permiten que las políticas públicas se consoliden o desestabilicen.Este artículo se enmarca en un abordaje socio-técnico proveniente de la sociología constructivista de la tecnología (Bijker, 1995; Pinch y Bijker, 2008; Thomas, 2008, Santos y Thomas, 2016), que combina herramientas de análisis de la sociología constructivista y del análisis de políticas públicas. La capacidad descriptiva y explicativa de un abordaje de este tipo deriva de la posibilidad de generar una reconstrucción analítica de las complejas relaciones entre usuarios y herramientas, actores y artefactos, instituciones y sistemas normativos, ideologías e intereses económicos, donde en el mismo acto en que se diseñan e implementan políticas públicas, se construyen órdenes jurídico-políticos, organizaciones sociales y sistemas tecno-productivos.Dos conceptos clave guían el análisis de este artículo: “funcionamiento/no funcionamiento” y “alianza socio-técnica”. El primero, es el resultado de un proceso de co-construcción social y normativa en el que intervienen, normalmente de forma auto-organizada, elementos heterogéneos: condiciones materiales, sistemas, conocimientos, regulaciones, financiamiento, prestaciones, etc. Supone complejos procesos de adecuación de respuestas/soluciones a concretas y particulares articulaciones socio-institucionales históricamente situadas. El segundo concepto, la alianza socio-técnica, es una reconstrucción analítica de una coalición de elementos heterogéneos implicados en el proceso de construcción de funcionamiento/no funcionamiento de una política pública. En otros términos, una alianza socio-técnica constituye un movimiento de alineamiento y coordinación de: artefactos, ideologías, regulaciones, conocimientos, instituciones, actores sociales, recursos económicos, condiciones ambientales, materiales, etc. que viabilizan o impiden la estabilización de la adecuación socio-técnica de una política y su funcionamiento.
Socio-technical alliances and drug policy: perspectives from the Argentinean Crisis of 2001
Keywords: Medicines; Public policies; Functioning/non-functioning; Socio-technical alliance; Medicamentos; Políticas públicas; Funcionamiento/no funcionamiento; Alianza socio-técnica; https://purl.org/pe-repo/ocde/ford#5.06.00